Inequality (un)perceived: the emergence of a discourse on economic inequality from the Middle Ages to the Age of Revolutions - Alfani, Guido; Frigeni, Roberta (Milan, 2013)
"Long-term developments in economic inequality are attracting growing attention. Earlier works focused on producing reliable measures of inequality, which overall suggest that in Europe, inequality levels were already high in preindustrial times and tended to grow almost continuously from the Middle Ages until the eve of the Industrial Revolution. Proposing a significantly different perspective, this article explores whether the change in inequality is connected to a change in how a condition of unequal distribution of property/income was perceived. By referring to large databases of manuscripts and printed editions covering ca. 1100-1830, we measure the occurrences of keywords connected to the notions of equality/inequality to determine when inequality became a topic considered worthy of specific reflection. Key texts are analyzed in depth to discover how and when such keywords acquired an economic meaning. Lastly, changes in meaning are connected to changes in levels of economic inequality. We demonstrate that the notions of equality/inequality appeared first in scholarly fields far from economic concerns and only slowly acquired economic meanings. This process intensified in the decades preceding the French Revolution of 1789, suggesting that changes in inequality levels contributed to brewing political upheaval in the Age of Revolutions."